Anti-icing performance of hydrophobic material used for electromechanical drill applied in ice core drilling. Issue 258 (10th August 2020) - Cao, Pinlu; Chen, Zhuo; Cao, Hongyu; Chen, Baoyi; Zheng, Zhichuan
Abstract: Using an anti-icing coating to prevent ice accretion on the drill surface is a feasible solution to address the drilling difficulties in warm ice. In this study, four types of commercially available hydrophobic coating materials were tested to evaluate their water repellency and anti-icing properties, namely, a mixture of silica and fluorocarbon resin with polytrifluoroethylene, modified Teflon, silica-based emulsion and an acrylic-based copolymer. Their water contact angles are 107°, 101°, 114° and 95°, respectively. All these hydrophobic coatings can significantly reduce the strength of the ice adhesion within a temperature range of −10 to −30°C on a planar or curved surface. The coating of an acrylic-based copolymer, in particular, can reduce the average tensile strength and the shear strength of the ice adhesion by 87.08 and 97.11% on planar surfaces at −30°C, and by 98.06 and 96.15% on a curved surface, respectively. The main challenge in the practical application of these coatings is their durability. An acrylic-based copolymer coating will lose its water repellency performance after 140 cycles of abrasion. The shear strength of ice adhered on curved surfaces coated with this material will approach that achieved on uncoated surfaces after 11 cycles of icing and de-icing tests.